2012
DOI: 10.1088/1367-2630/14/8/083021
|View full text |Cite
|
Sign up to set email alerts
|

A strange weak value in spontaneous pair productions via a supercritical step potential

Abstract: We consider a case when a weak value is introduced as a physical quantity rather than as an average of weak measurements. The case we treat is a time evolution of a particle by the 1 + 1-dimensional Dirac equation. In particular, in a spontaneous pair production via a supercritical step potential, a quantitative explanation can be given by a weak value for the group velocity of the particle. We also show that the condition for the pair production (supercriticality) corresponds to the condition when the weak va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Our result shows one of the interesting cases in which a weak value emerges as a real value of a physical quantity like [17]. In addition, aside from the issue of a weak value, it also gives a new insight into graphene in the sense that the creation process is related to virtual particles allowed by the uncertainty relations.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our result shows one of the interesting cases in which a weak value emerges as a real value of a physical quantity like [17]. In addition, aside from the issue of a weak value, it also gives a new insight into graphene in the sense that the creation process is related to virtual particles allowed by the uncertainty relations.…”
Section: Introductionmentioning
confidence: 64%
“…In [17], we showed the case when a group velocity of a quantum particle was given by a weak value in the 1 + 1 dimensional Dirac equation, which was applied to a transmission through a supercritical step potential. In this paper, we show that this weak-value formalism is also valid for describing the creation process of an electric carrier in graphene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weak value has been observed as an ensemble average via weak measurement so far, while weak value can also appear as a physical value in some cases [13][14][15][16][17]. In fact we have experimentally estimated weak values by the statistical procedure.…”
Section: Resultsmentioning
confidence: 85%
“…Although the weak value of −1 cannot be interpreted as a conventional probability, any weak value can be observed by weak measurements; it also naturally appears in a quantum phenomenon as a value of a physical quantity [31][32][33][34][35]. Recently we have also showed that positive and negative weak values are associated with symmetrical operations [36].…”
mentioning
confidence: 96%